The Influence of Computer Assisted Language Learning (Call) to Improve English Speaking Skills (Research, Society and Development, 2019)
The use of technology in learning has grown rapidly. One of them is learning English using Computer Assisted Language Learning or CALL. CALL is a computer-aided learning media used in the field of education which easy to access, spread and stored. Afterwards, this study tried to determine the influence of CALL media with lecture method and discussion to improve the cadets’ English speaking ability. This study used quantitative approach and descriptive quantitative analysis that revealed the problems occurred during the English learning. Statistical analysis is used by reviewing the learning process which were involving 50 cadets in both class A and B. The findings showed a significant difference of the use of CALL media in lecture method and discussion on English speaking skill.